2011
DOI: 10.1017/s0029665111003181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interaction betweenPPARG,PPARAandADIPOQgene variants and dietary fatty acids on plasma lipid profile and adiponectin concentration in a large intervention study

Abstract: Unsaturated fatty acids are ligands of PPAR-γ, which up-regulates genes involved in fatty acid transport and TAG synthesis and the insulin-sensitising adipokine adiponectin, which activates fatty acid β-oxidation via PPAR-α action in liver. We investigated the effect of dietary fatty acid interaction with PPARG, PPARA and ADIPOQ gene variants on plasma lipid and adiponectin concentrations in the Reading Imperial Surrey Cambridge King's study, a five-centre, parallel design, randomised controlled trial of 466 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 137 publications
(215 reference statements)
2
32
0
Order By: Relevance
“…Female gender was the variable with the stronger effect. Several other studies support our result that adiponectin concentration is higher in women than in men [14,27,30]. This difference is probably due to a direct effect of androgens on the synthesis of adiponectin [29].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Female gender was the variable with the stronger effect. Several other studies support our result that adiponectin concentration is higher in women than in men [14,27,30]. This difference is probably due to a direct effect of androgens on the synthesis of adiponectin [29].…”
Section: Discussionsupporting
confidence: 90%
“…Warodomwichit et al [16] found that -11391A allele carriers had significantly higher adiponectin levels and lower weight, BMI, and waist and hip circumferences, whereas in the study of AlSaleh et al [14] in subjects with different ethnicities there were no genotype-related differences. These discrepancies may be due to the interaction between the genetic variants and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies suggest that association between the genotype and BMI may depend on obesity (Ek et al 1999), age (Pihlajamaki et al 2004), dietary uptake of monounsaturated fatty acids (Garaulet et al 2011), and dietary ratio of polyunsaturated to saturated fatty acid (P/S ratio) (Luan et al 2001). Interestingly, dietary P/S ratio has also been shown to have an interaction with PPARG genotype on the effect on serum lipids in cross-sectional studies (Alsaleh et al 2011;Bouchard-Mercier et al 2011), and also in an intervention trial in which saturated fatty acid was replaced by monounsaturated fatty acid (AlSaleh et al 2012). Accordingly, animal studies suggest a complex interaction between PPARG2 and dietary fat.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with increased cellular proliferation, the activity of the tumour suppressors SMARCB1 (Modena, Lualdi et al 2005), RB1 and RBL2 (Villanueva 2014) and pro-apoptosis gene BNIPL3 (Diwan, Koesters et al 2008) was predicted to be inhibited. The activity of PPARA and PPARG, key regulators of fatty acid metabolism (AlSaleh, Sanders et al 2012) and transcriptional regulation (Salter and Tarling 2007) and the T-cell marker, CD3 as well as IRGM, an up-regulated gene in day 2 samples and day 7 feet, were also predicted to be inhibited in lymph nodes at day 7.…”
Section: Ingenuity Pathway Analysis Of Upstream Regulatorsmentioning
confidence: 99%